Efetividade do uso de andrógenos atenuados no tratamento doangioedema hereditário: 10 anos de acompanhamento no Ambulatório de Imunodeficiências Primárias do Hospital das Clínicas UFMG - Fernanda Gontijo Minafra (2013)
Background: Hereditary angioedema (HAE] is a painful, unpredictable, limiting and potentially fatal disease. The Challenge beCOmeS even greater when we deal with the lack Ofknowledge about the disease and therefore the lack Of adequate treatments. Attenuated androgens are the mOst widely available treatment in the prevention Of angioedema attacks in Our midst. Objectives TO describe the effectiveness and side effects Of the 1Ongterm treatment with attenuated androgens in patients diagnosed with HAE wh0 are mOnit0red in the Primary Immunodeficiency Ambulatøry at Hospítal das Clínicas da Universidade Federal de Minas Gerais [HC-UFMG). Specifically, to describe the frequency Of the Crisis beføre and after the treatment with danazol, its Side effects in patients using this medication Ín l0ngterm prophyiaxis and their acceptance Of the medication. Methous: An Observational Cehort Study was Conducted with patients diagnosed with HAE and mOnitOred at HCUFMG. They were evaluated Clinically and in laboratory and then Submitted t0 a Standardized questionnaire. The Collection Of data was assembled intO a database and a descriptive analysis Of it was performed. The data was expressed through measures Of central tendency and dispersion, accordíng tO the variable type. Continuous variables that showed variation Coefficients greater than 0.5 were expressed as median and interquartile range 25-75% (IQ). COntinuOuS variables with normal distribution were expressed as average and Standard devíation (SD). Variables Such as frequency and Severity Of Symptoms before and after danazol, side effects associated with its use and the acceptance Of the medication by the patients were studied. Results: 61 patients diagnosed with HAE were evaluated. The maximum time hetween beginning Of the Symptoms and the díagnosis was 60 years, with median Of 12 years (IQ 4-26]. From these patients, 45 (73.8%] made C0ntinuOuS use Of danazol, 5 (8.2%] used Only during the crisis and 11 (18%) never used the medícation. After the beginníng Of the lOngterm treatment, a medían Of 0.28 (IQ 0 1,2] Crísís per year was Observed md 18 (40%] patíents became totally asymptomatíc. The benefít was also Observed Ín the reductíon Of the severíty Of the Crísís, wíth a decrease în the need Of hospitalízatíon t0 8 (13.1%) Of theses patíents, compareci wíth 54 (88.5%] before they were mOnít0red. The síde effects assocíated wîth the use Of the medícatíon were Observed ín 35 (77.8%] patients submítted tO lOngterm use. The m0st expressíve alteratíons were weíght gain ín 29 (64.4%] patíents, menstrual Írregularitíes Ín 18 (56.2%), dislípídemia Ín 19 (65.5%) and líver funCtíOn's alteratíons Ín 8 (27.6%) among th0se patíents wh0 díd Complementary exams. The acceptzmce Of medícatíon was Cønsidered gOOd Or very gOOd by 32 (71.1%] patíents and none Of them had tO díscontínue usíng the medícatíon because Ofíts síde effects. Conclusions: The lack Of knowledge about the dísease Ís ah Ímportant íssue, as thís reflects in the time taken before the diagnosís, delaying the use Of appropriate therapy. Danazol ÍS necessary in the treatment Of m0st patíents and Íts presents well descríbed benefíts. There are relevant Sîde effects asseciated with the use Of this medíctíon, whích increzses the need tO use the mínima] effectíve dose. The acceptance Of the medícation by the patíents ís Considerably hígh, possíbly due tO an ímprovement Ín the qualíty Of lífe gaíned duríng the treatment.